Examining Job Satisfaction and Turnover Intent among Lawyers in the Maldivian Public Sector: Job Satisfaction and Turnover Intent among lawyers - Naeem, Shafeega; Jusoh, Mazuki; Khatibi, Ali; Azam, S.M. Ferdous (Polaris Global Journal of Scholarly Research and Trends, 2025)
Purpose: The primary objective of this paper is to ascertain how job satisfaction influences the reduction of turnover intention among lawyers in the public sector in the Maldives. Design/ Method/ Methodology: Employing a quantitative research design, the study adopts a cross-sectional data collection approach, gathering data from 218 public-sector lawyers in the Maldives. Findings: The analysis shows a significant negative relationship between job satisfaction and turnover intention. Implications: The findings provide valuable insights for organizations aiming to improve their human resource management practices, particularly within the legal profession. Implementing strategies to enhance job satisfaction among lawyers could serve as a key mechanism for reducing turnover and fostering a more stable and productive workforce in public sector organizations.